Association of Anti-Ro/Sjögren’s syndrome type A Antibodies and Complete Atrioventricular Block in an Adult With Sjögren’s Syndrome - Weng Kin TAM; Hui Ching HSU; Ming Hsiung HSIEH; Jong Shiuan YEH; Weng Chio TAM (Archives of Rheumatology, 2018)
A 57-year-old female patient with underlying hypertension, dyslipidemia, membranous glomerulonephritis, and Sjögren’s syndrome presented to our clinic with near-syncope and dizziness symptoms. We detected non-conducted sinus beat in 12-lead electrocardiography. An echocardiography showed that the left ventricular systolic function was preserved without a regional wall abnormality. The patient did not have symptoms of congestive heart failure or recent myocardial infarction. We observed complete atrioventricular block with longest pause of 6.2 seconds in a 24-hour Holter electrocardiography, and subsequently implanted a permanent pacemaker. Anti-Ro/Sjögren’s syndrome type A antibodies are commonly seen in Sjögren’s syndrome and associated with a neonatal complete heart block. The pathogenesis of anti-Ro/Sjögren’s syndrome type A antibodies in the conduction system of an adult heart is still uncertain. In this article, we report Sjögren’s syndrome in an adult patient with complete atrioventricular block and membranous glomerulonephritis, which may be associated with a positive titer of anti-Ro/Sjögren’s syndrome type A antibodies.